2009
DOI: 10.1007/s00421-009-1277-1
|View full text |Cite
|
Sign up to set email alerts
|

Ventilatory function in breath-hold divers: effect of glossopharyngeal insufflation

Abstract: This study was conducted to determine whether ventilatory parameters would change in breath-hold divers (BHDs) after they performed the glossopharyngeal technique for lung insufflation. Fifteen elite BHDs, 16 non-expert BHDs and 15 control subjects participated in this cross-sectional study. Volumes and expiratory flow rates were measured twice, before and after the glossopharyngeal technique performed at rest. Before the technique, greater forced vital capacity (FVC) and forced expiratory volume in 1 s (FEV(1… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
15
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(19 citation statements)
references
References 34 publications
4
15
0
Order By: Relevance
“…Similarly to our findings, other studies have also found higher measured FVC [5,[8][9][10]19] and FEV 1 [5,19] in divers than those predicted using population data. There is a good correlation between higher measured than predicted FVC and diving depth and length of professional diving career, i.e., the greater the length of time practicing diving and the greater the depth, the greater the difference between the measured values and the predicted values [9].…”
Section: Discussionsupporting
confidence: 92%
See 2 more Smart Citations
“…Similarly to our findings, other studies have also found higher measured FVC [5,[8][9][10]19] and FEV 1 [5,19] in divers than those predicted using population data. There is a good correlation between higher measured than predicted FVC and diving depth and length of professional diving career, i.e., the greater the length of time practicing diving and the greater the depth, the greater the difference between the measured values and the predicted values [9].…”
Section: Discussionsupporting
confidence: 92%
“…Some authors suggest that the increase in lung volume found in competitive free divers may be a result of an increase in the number of alveoli or the alveolar size by the virtue of training [20,21]. Others, have attributed the increase in lung volumes to the improved performance of the respiratory muscles gained from free diving or from GI [19,22,23]. This condition may be related to our findings, since the free-diving fishermen, who participated in this study, perform repetitive apneas for three to five hours on a daily basis in hyperbaric conditions at depths ranging from 8 to 15 m deep according to the tide (Figure 1).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Such incongruence may happen physiologically and may be accentuated by several mechanisms, including in utero exposures such as tobacco smoke or vitamin D deficiency (34,35), although it is unclear whether these effects would persist later in childhood. Chronic hypoxemia has been associated with a higher risk of dysanaptic lung growth (36); dysanapsis may also be present in breathhold divers, who use glossopharyngeal insufflation to force their lung volumes above TLC (providing extra oxygen and preventing compression when diving) (37). Compensatory lung growth after pneumonectomy may also be dysanaptic (38).…”
Section: Discussionmentioning
confidence: 99%
“…58 Furthermore, the FEV1/FVC ratio was normal, and identical in the two groups, indicating no increase in airway resistance and lack of signs of airway obstruction in divers. Nevertheless, even higher static and dynamic lung volumes were reached in subjects who performed glossopharyngeal breathing manoeuvres [13,22,23]. However, it was recently demonstrated that this practice may indeed lead to traumatic lung lesions, eventually resulting in pneumomediastinum or pneumothorax [24].…”
Section: Discussionmentioning
confidence: 99%